The Role of Re-Appropriation in Open Design: A Case Study on How Openness in Higher Education for Industrial Design Engineering Can Trigger Global Discussions on the Theme of Urban Gardening - Ostuzzi, Francesca; Conradie, Peter; De Couvreur, Lieven; Detand, Jan; Saldien, Jelle (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This case study explores the opportunities for students of Industrial Design Engineering to engage with direct and indirect stakeholders by making their design process and results into open-ended designed solutions. The reported case study involved 47 students during a two-weeks intensive course on the topic of urban gardening. Observations were collected during three distinctive phases: the co-design phase, the creation of an open design, and the sharing of these design solutions on the online platform Instructables.com. The open sharing of local solutions triggered more global discussions, based on several types of feedback: from simple questions to reference to existing works and from suggestions to critiques. Also, some examples of re-appropriation of the designed solutions were reported. These feedbacks show the possibilities for students to have a global vision on their local solutions, confronting them with a wider and more diverse audience. The case study shows, on the other hand, the difficulty in keeping students engaged in this global discussion, considering how after a few weeks the online discussions dropped to an almost complete silence. It is also very difficult with such online platforms to follow the re-appropriation cycles, losing the possibility of exploring the new local context where the replication/modification of the designed product occurred. The course’s focus on open design is interesting from both the design and educational points of view. It implies a deep change in the teaching approach and learning attitude of students, allowing unknown peers to take part in the design process and fostering a global discussion starting from unique and local solutions.